A new temperate deepwater skate of the genus Bathyraja (Rajoidei: Arhynchobatidae) from the South-West Pacific - Last, Peter R.; Stewart, Andrew L.; Séret, Bernard (Zootaxa, 2016)
A single specimen of a new Bathyraja skate was collected by the authors in 2003 during a survey of the deepwater biota of the northern Tasman Sea by the New Zealand FRV Tangaroa. This skate, labelled the ‘blonde skate’ by voyage participants, is uniformly white on all surfaces of the body and the skin is partly translucent. It belongs to a subgroup of Bathyraja with a large, almost smooth, quadrangular disc and well-developed and equally spaced median tail thorns. Other similar and probably closely related Bathyraja specimens have been caught in seas to the south of New Zealand since the discovery of this species, but their identity is yet to be confirmed.